Exploring Of Students’ Difficulties In Reading Section Of Toefl - Nazriani Lubis; Nur Pajri Hidayah Siregar (Cybernetics: Journal Educational Research and Social Studies, 2022)
This research discussed the difficulties in reading section of TOEFL test by the students. This research used qualitative method with a thematic analysis approach.The instrumental of this research was EFL students learning outcomes and Interview. This research was carried out at Universities Muslim Nusantara Muslim Al-Washliyah Medan. The subject of this research there were 3 semester 8 students chosen as the participants of the research. The criteria as follows 1 student with higher TOEFL score, 1 student with moderate TOEFL score, and 1 student with lower TOEFL score. The result of research was found namely; vocabulary, fluency, and reasoning and background knowledge. That there are themes namely kinds of vocabulary; reading speed and background knowledge the students need to repeat reading the text for more than 5 times in order to find out the meaning for the unfamiliar vocabulary. The spesific vocabulary such as : science, health and nature phenomena. In this care the students with lower TOEFL score found that lack background knowledge make them being slower in reading the text